A Study of Clinical and Laboratory Profile of Dengue Fever in Tertiary Care Hospital in Central Karnataka, India (Global Journal of Medical Research, 2014)
Abstract not found
Keywords: dengue; dengue virus; seropositive; bleeding manifestations